In quest of a shared planet : negotiating climate from the Global South - Khan, Naveeda Ahmed, 1969- (Fordham University Press, 2023)
"...In Quest of a Shared Planet is a stirring call to action that highlights the key role responsive and active youth have in climate negotiations. It is an invitation not only to understand the climate negotiation process but also to navigate and critique it, with sympathy and an eye to viable alternatives."--Back cover